Does Monetary Incentives Have Stronger Influence on Workers’ Productivity Other Than Any Form of Motivational Incentives? - Daramola, Adedeji Adebola; Daramola, Lilian (International Journal of Business and Management Future, 2019)
An incentive is a reward given to a person to stimulate his or her actions to a desired direction. It has motivational powers and is widely utilized by small and large organizations to motivate employees. These incentives can either be monetary or non-monetary. The aim of this study is to find out whether monetary incentives has a stronger influence on workers productiveness other than any form of motivational incentives, using a case study of BORBDA. In order to achieve this, questionnaire was designed, processed and analyzed using Chi-Square. The study revealed that monetary incentives do not exert stronger influence on workers’ productivity than any other form of motivational factor. In view of this, money is not the only motivating factor that has stronger influence on workers’’ productivity, as there are other forms of motivational incentives for employees. The head of organization should look inward for better incentives to motivate their employees without necessarily using monetary incentives.